1994
DOI: 10.1084/jem.179.1.341
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD2 receptor and anti-CD2 ligand (CD48) antibodies synergize to prolong allograft survival.

Abstract: SummaryIndefinite graft survival was obtained with murine cardiac allografts using the combined administration of monoclonal antibodies (mAbs) directed against the receptor ligand pair CD2-CD48. Although each antibody could prolong graft survival when given alone, neither resulted in the indefinite graft survival seen with the combination. Combined mAb administration is associated with inhibition of T cell priming and help and subsequent cytotoxic T lymphocyte generation. This indicates that the interaction be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
59
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(59 citation statements)
references
References 25 publications
0
59
0
Order By: Relevance
“…Various immunosuppressive molecules have been tested in a variety of transplantation models and need to be assessed for their effectiveness on graft prolongation. In one of the strategies examined, the blockade of co-stimulatory signals by immunosuppressive proteins has been shown to prolong allograft survival in various transplantation settings [10,11]. In T cell-mediated immunity, the full activation of naïve T cells requires co-stimulatory signals generated by the ligation of CD28 on T cells with their receptor, B7-1/B7-2, on antigen-presenting cells (APCs) [12].…”
mentioning
confidence: 99%
“…Various immunosuppressive molecules have been tested in a variety of transplantation models and need to be assessed for their effectiveness on graft prolongation. In one of the strategies examined, the blockade of co-stimulatory signals by immunosuppressive proteins has been shown to prolong allograft survival in various transplantation settings [10,11]. In T cell-mediated immunity, the full activation of naïve T cells requires co-stimulatory signals generated by the ligation of CD28 on T cells with their receptor, B7-1/B7-2, on antigen-presenting cells (APCs) [12].…”
mentioning
confidence: 99%
“…the average of the spectral density function at the proton frequency as well as the sum and difference of the proton and nitrogen frequencies; T , , overall tumbling time; GlcNAc-I , N-acetylglucosamine. vation signals that synergize with those mediated by the TCR (Meuer et al, 1984;Bierer et al, 1988), and in vivo studies in rodents have shown that administration of anti-CD2 monoclonal antibodies effectively prolong allograft survival (Chavin et al, 1993;Qin et al, 1994). Moreover, the CD2-CD58 pathway plays a critical role in the maintenance and reversal of anergy (BoussiOtis et al, 1994), and anti-CD2 and anti-CD58 mAbs can specifically inhibit interleukin-12-induced proliferation and interferon y production by activated T cells (Gollob et al, 1995).…”
mentioning
confidence: 99%
“…The cytoplasmic domain of CD5 has an immunoreceptor tyrosine-based inhibition motif (ITIM) and has been shown to negatively regulate signaling through both the TCR and BCR [27,29]. In vitro and in vivo studies with anti-CD2 antibodies revealed inhibition of T cell function, including longlasting hyporesponsiveness, that could not be entirely explained simply by blockade of CD2 interactions with its ligand [30,31]. Thus, both CD2 and CD5 appear capable of antagonizing T cell activation, whereas in contrast, CD28 has only been reported to augment mature T cell activation.…”
Section: Discussionmentioning
confidence: 99%